PENGARUH MODEL PEMBELAJARAN PBL UNTUK MENGATASI KESULITAN SISWA DALAM MENYELESAIKAN SOAL BENTUK ALJABAR MTS PAB3 - Setia, Nur; Rambe, Imelda Wardani (Universitas Bhinneka PGRI, 2023)
The problem in this study is the difficulty of class VII MTs PAB 3 students in solving materials for algebra form material. This study aims to find out whether there is the effect of the Problem Based Learning (PBL) learning model to overcome the difficulties of students in completing the Algebra Form Material Problem in Class VII MTs PAB 3. This type of research is a pre-experimental design research with one group pre-test research design Post-test. The population in this study was all students of Class VII MTs PAB 3, while the sample of this study consisted of one class totaling 30 students. Data in this research was analyzed using the t test. From the t test analysis obtained which is larger than the value of so that is accepted and is rejected, meaning that there is a significant influence between the learning model of Problem Based Learning (PBL) to overcome students' difficulties in solving algebraic material problems. Then it can be concluded that there is an influence of the Problem Based Learning (PBL) learning model to overcome students' difficulties in solving algebraic material questions in class VII MTs PAB 3.